A opinião do auditor importa? Um estudo experimental sobre o impacto na decisão dos investidores não institucionais - Miranda, Débora Vieira (2023)
The purpose of this research was to verify the impact of the modified audit opinion on the judgment and investment decision-making of Brazilian non-institutional investors. There is a consensus among society in general that auditing ensures companies' financial reports, as well as communicating the economic and equity situation of these organizations through the Independent Auditor's Report (IAR) and, in this way, provides information and subsidies for economic agents to make rational decisions based on this disclosure. In this sense, the Inspired Confidence Theory stands out, in which the auditing activity, through the IAR and the audit opinion, attributes confidence and credibility to the financial statements of companies (Aziz et al, 2014). The accounting scandals of recent decades, however, have led to criticism of the information content of the IAR. For this reason, international organizations such as the IAASB and national ones such as the CFC have promoted regulatory changes that have modified the structure of the IAR in order to increase its usefulness, among which NBC TA 700 (ISA 700) and NBC TA 705 (ISA 705) stand out. These changes gave even more focus to the auditor's opinion, which was moved from the third paragraph to the first paragraph of the IAR (Prasad & Chand, 2017), giving it primacy and making its readers attentive to its content (Cordos et al., 2020; Simnett & Huggins, 2014). Furthermore, in Brazil, the category of non-institutional investors in capital markets has grown in recent years. In this context, we carried out an experiment with a quantitative approach, with a 2x1 between-subjects design, manipulating (i) Unqualified Audit Opinion and (ii) Qualified Audit Opinion, in which the participant made an investment decision based on a hypothetical experimental scenario. The analysis techniques used were descriptive statistics, WilcoxonMann-Whitney, Kruskal-Wallis and marginal effects graphs, using R software to analyze the data. The results indicated that the qualified audit opinion had a negative impact on the decision making of Brazilian non-institutional investors, but had no significant effect on the percentage values of investments. On the other hand, the sensitivity analysis demonstrated that the adverse audit opinion and the abstention of an audit opinion affected both investment decision-making and the percentage values of investments. These findings have the potential to contribute to non-institutional investors, regulators, auditors, and academics, as they add knowledge regarding the usefulness of RAI in its model in force as of 2016.